Burkholderia cepacia in cystic fibrosis children and adolescents: overall survival and immune alterations - Shmarina, Galina; Pukhalskaya, Daria; Shmarin, Vassiliy; Semykin, Sergey; Avakyan, Lusine; Krasovsky, Stanislav; Goryainova, Anastasia; Kostyuk, Svetlana; Zinchenko, Rena; Kashirskaya, Nataliya (Frontiers in Cellular and Infection Microbiology, 2024)
Background: In current literature there are only scarce data on the host inflammatory response during Burkholderia cepacia complex (Bcc) persistence. The primary objective of the present research was to carry out cross-sectional analyses of biomarkers and evaluate disease progression in cystic fibrosis (CF) patients with chronic Bcc infection and pathogen-free ones. The secondary aim was to assess prospectively overall survival of the study participants during up to 8 years of follow-up. Methods: The study included 116 paediatric patients with CF; 47 CF patients were chronically infected with Bcc, and 69 individuals were Bcc free.